P-type zeolite converted from mordenite and preparation method of P-type zeolite

By adding calcium-containing substances to the hydrothermal system to prepare P-type zeolite, the problems of decreased selectivity and high synthesis cost of mordenite are solved, and efficient adsorption of Sr, Co and Mn ions is achieved, making it suitable for nuclear power plant wastewater treatment and contaminated site remediation.

CN120774437APending Publication Date: 2025-10-14SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510906288.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, the selectivity of mordenite decreases when adsorbing large molecules or highly polar substances, and the method of synthesizing P-type zeolite is costly and time-consuming. Traditional adsorption materials have low adsorption capacity and insufficient ion exchange performance, and cannot effectively adsorb large molecules and radionuclides in water.

Method used

By adding calcium-containing substances into the hydrothermal system, mordenite is mixed with calcium oxide, calcium chloride or calcium carbonate powder and NaOH solution, and P-type zeolite is prepared after hydrothermal modification. The reaction temperature and time are controlled, the concentration of the alkaline solution is reduced, and the aluminosilicate skeleton is promoted to form a P-type zeolite structure.

Benefits of technology

The preparation cost of P-type zeolite is reduced and production efficiency is improved. The synthesized P-type zeolite has excellent selective adsorption properties for Sr, Co and Mn ions, and is suitable for nuclear power plant wastewater treatment, contaminated site remediation and water treatment, which is in line with the concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120774437A_ABST
    Figure CN120774437A_ABST
Patent Text Reader

Abstract

The invention discloses P-type zeolite converted from mordenite and a preparation method thereof, and the method comprises the following steps: step 1, mixing 5g of mordenite with 0.05-0.5 g of calcium-containing substance, adding into 50mL of NaOH solution with the concentration of 1-2M, and stirring to uniformly mix to obtain a precursor mixture; and 2, carrying out hydrothermal modification on the precursor mixture at 95-105 DEG C for 6-12 hours, and sequentially carrying out suction filtration, drying and grinding to obtain the P-type zeolite. According to the invention, the preparation cost of the P-type zeolite is reduced, and the synthesized P-type zeolite has excellent selective adsorption performance on Sr, Co and Mn ions in water.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the modification of mordenite, in particular a P-type zeolite converted from mordenite and a preparation method thereof. BACKGROUND

[0002] With the transformation of global energy structure and the demand for low-carbon development, nuclear energy as a clean and efficient energy form has been rapidly developed worldwide. However, the radionuclides produced in the process of nuclear energy utilization, such as strontium (Sr), cesium (Cs) and cobalt (Co), pose a potential threat to the environment and human health. These radionuclides often have extremely long half-lives and most of them are highly toxic. Currently, the treatment technologies for radionuclides mainly include chemical precipitation, ion exchange, membrane separation and adsorption, etc. For the chemical precipitation method, although the operation is simple, a large amount of secondary waste is generated; for the ion exchange method, the ion exchange resin has good selectivity, but the cost is high; for the membrane separation method, there are problems of high energy consumption and easy pollution. In comparison, the adsorption method is concerned due to its simple operation, low cost and strong adaptability. However, conventional adsorption materials such as activated carbon and clay minerals often have problems of low adsorption capacity, poor selectivity and insufficient radiation resistance, etc. Therefore, the development of new high-efficiency adsorption materials has become a hot research topic.

[0003] Mordenite is a member of the zeolite family, which is a microporous material with unique structure and excellent performance. It has a high specific surface area and uniform pore size distribution. Its crystal structure is composed of silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra, forming regular channels and cavities, including main channels with a diameter of about 0.65×0.70 nm and side channels with a diameter of 0.26×0.57 nm. This multi-level pore structure enables it to adapt to radionuclide ions of different sizes, endowing mordenite with excellent adsorption, ion exchange and catalytic performance, and it is widely used in nuclear power plant wastewater treatment, contaminated site remediation, gas separation, water treatment, petroleum chemical industry and environmental protection, etc. In addition, mordenite is prepared through strict synthesis and purification processes, with extremely low impurity content and more stable performance, which can meet the needs of high-end industrial applications. However, mordenite also has some limitations in adsorption, such as limited adsorption capacity for some macromolecules or highly polar substances, and possible decrease in selectivity in high humidity or complex component environments. Moreover, its adsorption capacity is limited by the pore size, which cannot effectively adsorb molecules with too large size. In addition, the high silicon-aluminum ratio of mordenite makes its ion exchange performance and adsorption performance for water-borne cations and other cations relatively low. Therefore, it is necessary to modify or develop composite materials to optimize its adsorption performance.

[0004] In recent years, some researchers have successfully synthesized P-type zeolite by interzeolite conversion, for example, Gao Chashan synthesized P-type zeolite from natural phillipsite under hydrothermal conditions, and our team also realized the conversion of natural epidesmine to P-type zeolite. P-type zeolite is a kind of silicate mineral, which is famous for its unique three-dimensional network framework structure and rich acid sites. The special structure endows it with high specific surface area, excellent adsorption performance and catalytic activity, as well as good thermal stability and chemical stability. These characteristics make P-type zeolite show excellent application potential in environmental protection, petroleum and fine chemical industries, especially in molecular sieve separation, catalysts and catalyst carriers. However, the current synthesis method of P-type zeolite has the problems of high synthesis temperature, high required alkali concentration and long required synthesis time, resulting in relatively high comprehensive cost. SUMMARY

[0005] The present application aims to provide a mordenite converted P-type zeolite and a preparation method thereof, which not only reduces the preparation cost of P-type zeolite, but also has excellent selective adsorption performance for Sr, Co and Mn ions in water.

[0006] The present application is realized by the following technical scheme:

[0007] A preparation method of a mordenite converted P-type zeolite, comprising the following steps:

[0008] Step 1, preparing a precursor mixture

[0009] 5g of mordenite is mixed with 0.05-0.5g of calcium-containing material, and 50mL of NaOH solution with a concentration of 1-2M is added, and stirring is performed to make the mixture uniform, to obtain a precursor mixture;

[0010] Step 2, preparing P-type zeolite

[0011] The precursor mixture is hydrothermally modified at 95-105℃ for 6-12h, and then is subjected to filtration, drying and grinding in sequence to obtain P-type zeolite.

[0012] Further, the calcium-containing material of step 1 is calcium oxide, calcium chloride or calcium carbonate powder.

[0013] A mordenite converted P-type zeolite, Ca 2+ The content of which is 3.22%-13.54%.

[0014] Further, the average particle size is 18.18-25.33μm.

[0015] Further, the silicon-aluminum ratio is 2.08-3.64.

[0016] Further, the P-type zeolite has excellent selective adsorption for Sr, Co and Mn ions in water, wherein the selectivity coefficients of adsorbing Sr ions with respect to Mg, K and Ca ions are 5.89-9.36, 1.02-1.49 and 2.13-6.23 respectively; the selectivity coefficients of adsorbing Co ions with respect to Mg, K and Ca ions are 5.42-15.22, 1.02-2.36 and 1.06-32.68 respectively; and the selectivity coefficients of adsorbing Mn ions with respect to Mg, K and Ca ions are 2.58-30.67, 1.05-2.93 and 1.15-13.66 respectively.

[0017] Further, the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 76.77-150.86 mg / g, 38.65-113.26 mg / g and 42.57-120.69 mg / g respectively.

[0018] The present application has the following beneficial technical effects:

[0019] Firstly, the present application adds calcium-containing substances in a hydrothermal system, which guides the formation of a cage-like structure of P-type zeolite from a silicate-aluminate framework in the hydrothermal process, and promotes the conversion of mordenite to P-type zeolite, thereby effectively reducing the concentration of alkali solution, the hydrothermal reaction temperature and the reaction time for the conversion of mordenite to P-type zeolite, reducing energy consumption, improving production efficiency and reducing production cost; secondly, the P-type zeolite prepared by using mordenite with extremely low impurity content as raw material and by controlling the reaction temperature and time has higher purity and excellent selective adsorption performance for radioactive nuclides; in summary, compared with the traditional method for producing P-type zeolite, the present application has the advantages of simple preparation process, easy-to-control reaction conditions and low cost, and the synthesized P-type zeolite has excellent selective adsorption for Co, Sr and Mn ions in water, showing obvious advantages in reducing environmental pollution, meeting the concept of green chemistry, and having important significance for nuclear power plant wastewater treatment, contaminated site remediation, water treatment and environmental protection. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 : XRD patterns of P-type zeolites prepared by the present application and the conventional method in Example 1;

[0021] Figure 2 : SEM images and EDS energy spectrum analysis results of P-type zeolites prepared by the present application and the conventional method;

[0022] Figure 3 : Adsorption capacity graphs of P-type zeolites prepared by the present application and the conventional method in Example 1 for Sr, Co and Mn ions in water;

[0023] Figure 4: Selective adsorption effect diagram of P-type zeolite prepared by the embodiment 1 and the conventional method on Sr ion in water;

[0024] Figure 5 : Selective adsorption effect diagram of P-type zeolite prepared by the embodiment 1 and the conventional method on Co ion in water;

[0025] Figure 6 : Selective adsorption effect diagram of P-type zeolite prepared by the embodiment 1 and the conventional method on Mn ion in water. DETAILED DESCRIPTION

[0026] The present application will be further described in conjunction with specific embodiments, which are explanations of the present application rather than limitations.

[0027] Embodiment 1

[0028] Step 1, preparation of precursor mixture

[0029] 5g mordenite and 0.25g calcium oxide powder were mixed, and then 50mL NaOH solution with a concentration of 2M was added, and stirring was performed to obtain a uniform mixture, thereby obtaining a precursor mixture;

[0030] Step 2, preparation of P-type zeolite

[0031] The precursor mixture was hydrothermally modified at 100℃ for 12h, and then was subjected to filtration, drying and grinding in sequence, thereby obtaining P-type zeolite.

[0032] From Figure 1 It can be seen that the characteristic peaks of the XRD spectrum of the product of the existing conventional hydrothermal reaction are mainly the characteristic peaks of mordenite and P-type zeolite, which indicates that the mordenite is not completely converted into P-type zeolite, while the characteristic peaks of mordenite completely disappear in the XRD spectrum of the hydrothermal reaction product of the embodiment 1 of the present application, and the intensity of the characteristic peaks of P-type zeolite is obviously improved, which indicates that the reaction conditions of the present application can promote the complete conversion of mordenite into P-type zeolite.

[0033] From Figure 2 It can be seen from (a) that the morphology of the P-type zeolite synthesized by the conventional method includes regular spheres and irregular ellipsoids, and the size of the particles is several tens of microns to several microns, and it can be found from the XRD spectrum analysis that only part of the mordenite is converted into P-type zeolite under the conventional hydrothermal conditions, and the irregular ellipsoids are unconverted mordenite particles, and from Figure 2 The EDS spectrum analysis result of (c) shows that the silicon-aluminum ratio is close to 4.26; from Figure 2 It can be seen from (b) that the morphology of the P-type zeolite synthesized by the present application is regular and uniform spherical or double spherical, and it can be known from the XRD spectrum analysis that the mordenite has been completely converted into P-type zeolite, and from Figure 2The EDS spectrum analysis result of (d) shows that the silicon-aluminum ratio is close to 2.13, and the silicon-aluminum ratio of the P-type zeolite synthesized by the present application is significantly reduced compared with the P-type zeolite synthesized by the conventional method.

[0034] From Figure 3 It can be seen that the adsorption capacity of the P-type zeolite prepared in Example 1 for Sr, Co and Mn ions in water is 150.86 mg / g, 110.48 mg / g and 120.69 mg / g respectively, which is significantly higher than the adsorption capacity of the P-type zeolite synthesized by the existing conventional method for Sr, Co and Mn ions in water, which is 76.99 mg / g, 30.53 mg / g and 34.41 mg / g respectively.

[0035] From Figure 4 It can be seen that the selectivity coefficient of the P-type zeolite prepared in Example 1 for adsorbing Sr ions relative to Mg, K and Ca ions is 9.36, 1.38 and 5.70 respectively.

[0036] From Figure 5 It can be seen that the selectivity coefficient of the P-type zeolite prepared in Example 1 for adsorbing Co ions relative to Mg, K and Ca ions is 15.07, 2.25 and 29.24 respectively.

[0037] From Figure 6 It can be seen that the selectivity coefficient of the P-type zeolite prepared in Example 1 for adsorbing Mn ions relative to Mg, K and Ca ions is 29.66, 2.84 and 11.47 respectively.

[0038] Example 2

[0039] Step 1, preparation of precursor mixture

[0040] 5g mordenite was mixed with 0.25g calcium chloride powder, 50mL of 2M NaOH solution was added, and stirring was performed to make the mixture uniform, to obtain a precursor mixture;

[0041] Step 2, preparation of P-type zeolite

[0042] The precursor mixture was hydrothermally modified at 100℃ for 12h, and then was subjected to filtration, drying and grinding in sequence to obtain the P-type zeolite.

[0043] The selectivity coefficients of the P-type zeolite prepared in Example 2 for adsorbing Sr ions relative to Mg, K and Ca ions are 9.08, 1.47 and 5.14 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 14.68, 2.32 and 30.05 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 27.24, 2.65 and 10.59 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 145.78 mg / g, 100.36 mg / g and 105.27 mg / g respectively.

[0044] Example 3

[0045] Step 1, preparing a precursor mixture

[0046] 5 g of mordenite was mixed with 0.25 g of calcium carbonate powder, and 50 mL of a 2M NaOH solution was added thereto, and the mixture was stirred to obtain a precursor mixture;

[0047] Step 2, preparing a P-type zeolite

[0048] The precursor mixture was hydrothermally modified at 100°C for 12 h, and then was subjected to filtration, drying and grinding in sequence to obtain a P-type zeolite.

[0049] The selectivity coefficients of the P-type zeolite prepared in Example 3 for adsorbing Sr ions relative to Mg, K and Ca ions are 9.22, 1.28 and 5.86 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 14.89, 2.23 and 30.48 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 27.25, 2.77 and 11.08 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 142.26 mg / g, 98.78 mg / g and 102.37 mg / g respectively.

[0050] Example 4

[0051] Step 1, preparing a precursor mixture

[0052] 5 g of mordenite was mixed with 0.05 g of calcium oxide powder, and 50 mL of a 2M NaOH solution was added thereto, and the mixture was stirred to obtain a precursor mixture;

[0053] Step 2, preparing a P-type zeolite

[0054] The precursor mixture was hydrothermally modified at 100°C for 12 h, and then was subjected to filtration, drying and grinding in sequence to obtain a P-type zeolite.

[0055] The selectivity coefficients of the P-type zeolite prepared in Example 5 for adsorbing Sr ions relative to Mg, K and Ca ions are 6.72, 1.08 and 3.26 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 6.36, 1.66 and 13.35 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 4.27, 1.87 and 7.63 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 95.58 mg / g, 60.88 mg / g and 62.57 mg / g respectively.

[0056] Example 5

[0057] Step 1, preparing a precursor mixture

[0058] 5 g of mordenite was mixed with 0.5 g of calcium oxide powder, and 50 mL of a NaOH solution with a concentration of 2M was added, and the mixture was stirred to be uniform, to obtain a precursor mixture;

[0059] Step 2, preparing a P-type zeolite

[0060] The precursor mixture was hydrothermally modified at 100°C for 12 h, and then was sequentially subjected to suction filtration, drying and grinding, to obtain a P-type zeolite.

[0061] The selectivity coefficients of the P-type zeolite prepared in Example 5 for adsorbing Sr ions relative to Mg, K and Ca ions are 8.09, 1.27 and 5.18 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 14.16, 1.96 and 25.57 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 26.79, 2.58 and 9.36 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 135.82 mg / g, 96.67 mg / g and 102.46 mg / g respectively.

[0062] Example 6

[0063] Step 1, preparing a precursor mixture

[0064] 5 g of mordenite was mixed with 0.5 g of calcium oxide powder, and 50 mL of a NaOH solution with a concentration of 2M was added, and the mixture was stirred to be uniform, to obtain a precursor mixture;

[0065] Step 2, preparing a P-type zeolite

[0066] The precursor mixture was hydrothermally modified at 100°C for 12 h, and then was sequentially subjected to suction filtration, drying and grinding, to obtain a P-type zeolite.

[0067] The selectivity coefficients of the P-type zeolite prepared in Example 6 for adsorbing Sr ions relative to Mg, K and Ca ions are 9.04, 1.49 and 6.23 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 13.22, 2.02 and 32.68 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 25.45, 2.76 and 13.66 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 142.56 mg / g, 99.56 mg / g and 103.28 mg / g respectively.

[0068] Example 7

[0069] Step 1, preparing a precursor mixture

[0070] 5g mordenite was mixed with 0.25g calcium oxide powder, 50mL of a NaOH solution with a concentration of 1M was added, and the mixture was stirred to be uniform to obtain a precursor mixture;

[0071] Step 2, preparing a P-type zeolite

[0072] The precursor mixture was hydrothermally modified at 100℃ for 12h, and then was sequentially subjected to suction filtration, drying and grinding to obtain a P-type zeolite.

[0073] The selectivity coefficients of the P-type zeolite prepared in Example 7 for adsorbing Sr ions relative to Mg, K and Ca ions are 6.43, 1.02 and 4.35 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 6.02, 1.18 and 20.27 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 4.18, 1.45 and 8.56 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 85.47 mg / g, 52.16 mg / g and 54.88 mg / g respectively.

[0074] Example 8

[0075] Step 1, preparing a precursor mixture

[0076] 5g mordenite was mixed with 0.25g calcium oxide powder, 50mL of a NaOH solution with a concentration of 2M was added, and the mixture was stirred to be uniform to obtain a precursor mixture;

[0077] Step 2, preparing a P-type zeolite

[0078] The precursor mixture was hydrothermally modified at 95℃ for 12h, and then was sequentially subjected to suction filtration, drying and grinding to obtain a P-type zeolite.

[0079] The selectivity coefficients of the P-type zeolite prepared in Example 8 for adsorbing Sr ions relative to Mg, K and Ca ions are 9.08, 1.22 and 5.45 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 14.37, 2.03 and 26.76 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 27.79, 2.65 and 10.08 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 146.66 mg / g, 103.27 mg / g and 115.69 mg / g respectively.

[0080] Example 9

[0081] Step 1, preparing a precursor mixture

[0082] 5 g of mordenite was mixed with 0.25 g of calcium oxide powder, 50 mL of a NaOH solution with a concentration of 2 M was added, and stirring was performed to uniformly mix the mixture, thereby obtaining a precursor mixture;

[0083] Step 2, preparing a P-type zeolite

[0084] The precursor mixture was hydrothermally modified at 105°C for 12 h, and then was sequentially subjected to suction filtration, drying and grinding, thereby obtaining a P-type zeolite.

[0085] The selectivity coefficients of the P-type zeolite prepared in Example 9 for adsorbing Sr ions relative to Mg, K and Ca ions are 9.32, 1.46 and 5.49 respectively; the selectivity coefficients for adsorbing Co ions relative to Mg, K and Ca ions are 15.22, 2.36 and 30.88 respectively; the selectivity coefficients for adsorbing Mn ions relative to Mg, K and Ca ions are 30.67, 2.93 and 11.56 respectively; and the adsorption capacities of the P-type zeolite for Sr, Co and Mn ions in water are 149.69 mg / g, 113.26 mg / g and 118.98 mg / g respectively.

[0086] Example 10

[0087] Step 1, preparing a precursor mixture

[0088] 5 g of mordenite was mixed with 0.25 g of calcium oxide powder, 50 mL of a NaOH solution with a concentration of 1.5 M was added, and stirring was performed to uniformly mix the mixture, thereby obtaining a precursor mixture;

[0089] Step 2, preparing a P-type zeolite

[0090] The precursor mixture was hydrothermally modified at 100°C for 9 h, and then was sequentially subjected to suction filtration, drying and grinding, thereby obtaining a P-type zeolite.

[0091] The P-type zeolite prepared in Example 10 has selectivity coefficients for Sr ions relative to Mg, K and Ca ions of 5.89, 1.48 and 5.46, respectively; selectivity coefficients for Co ions relative to Mg, K and Ca ions of 5.45, 2.08 and 16.88, respectively; selectivity coefficients for Mn ions relative to Mg, K and Ca ions of 4.36, 1.88 and 9.76, respectively; and the adsorption capacities for Sr, Co and Mn ions in water are 80.69 mg / g, 52.43 mg / g and 56.57 mg / g, respectively.

[0092] Example 11

[0093] Step 1: Prepare the precursor mixture

[0094] 5 g of mordenite and 0.25 g of calcium oxide powder were mixed, added to 50 mL of 1 M NaOH solution, and stirred to mix evenly to obtain a precursor mixture;

[0095] Step 2: Preparation of P-type zeolite

[0096] The precursor mixture was hydrothermally modified at 100° C. for 6 h, and then filtered, dried and ground in sequence to obtain P-type zeolite.

[0097] The P-type zeolite prepared in Example 11 has selectivity coefficients for Sr ions relative to Mg, K and Ca ions of 5.98, 1.11 and 2.13, respectively; selectivity coefficients for Co ions relative to Mg, K and Ca ions of 5.42, 1.02 and 1.06, respectively; selectivity coefficients for Mn ions relative to Mg, K and Ca ions of 2.58, 1.05 and 1.15, respectively; and adsorption capacities for Sr, Co and Mn ions in water of 76.77 mg / g, 38.65 mg / g and 42.57 mg / g, respectively.

[0098] The physical parameters of the P-type zeolite converted from mordenite synthesized in Examples 1 to 11 and the P-type zeolite synthesized by the conventional method are shown in Table 1. As can be seen from Table 1, the P-type zeolite converted from mordenite synthesized in Examples 1 to 11 of the present invention has a higher calcium ion content, a larger average particle size, and a lower silicon-aluminum ratio than the P-type zeolite synthesized by the conventional method. Specifically, the higher the calcium ion content, the more optimized the pore structure and pore size distribution of the zeolite, and the less inclined the P-type zeolite to adsorb calcium ions in water, thereby exhibiting good selective adsorption performance for Sr, Co, and Mn ions. The low silicon-aluminum ratio gives the P-type zeolite good ion exchange performance and better adsorption effect for cations in water.

[0099] Table 1 Physical parameters of the P-type zeolites synthesized in Examples 1 to 11 and existing P-type zeolites

[0100] Sample Ca ion content Average particle size Silica alumina ratio Example 1 11.23 23.55 2.13 Example 2 11.46 22.87 2.64 Example 3 11.18 23.11 2.55 Example 4 3.22 18.18 3.64 Example 5 7.93 20.88 2.74 Example 6 13.54 25.33 2.15 Example 7 11.05 20.17 2.82 Example 8 11.31 23.15 2.18 Example 9 11.28 23.63 2.08 Example 10 11.14 22.33 2.42 Example 11 10.92 22.36 3.24 Conventional approach 0.55 3.0 4.26

Claims

1. A method for preparing P-type zeolite converted from mordenite, characterized in that: The steps include: Step 1: Prepare the precursor mixture 5 g of mordenite and 0.05-0.5 g of calcium-containing material were mixed, added to 50 mL of 1-2 M NaOH solution, and stirred to mix evenly to obtain a precursor mixture; Step 2: Preparation of P-type zeolite The precursor mixture is hydrothermally modified at 95-105° C. for 6-12 hours, and then filtered, dried and ground in sequence to obtain P-type zeolite.

2. The method for preparing P-type zeolite converted from mordenite according to claim 1, characterized in that: The calcium-containing substance in step 1 is calcium oxide, calcium chloride or calcium carbonate powder.

3. A P-type zeolite converted from mordenite prepared by the method according to claim 1 or 2, characterized in that: Ca 2+ The content is 3.22%~13.54%.

4. The P-type zeolite converted from mordenite according to claim 3, characterized in that: The average particle size is 18.18~25.33μm.

5. The P-type zeolite converted from mordenite according to claim 3, characterized in that: The silicon-aluminum ratio is 2.08 to 3.

64.

6. The P-type zeolite converted from mordenite according to claim 3, characterized in that: It has excellent selective adsorption for Sr, Co and Mn ions in water, among which: the selectivity coefficients of Sr ion adsorption relative to Mg, K and Ca ions are 5.89-9.36, 1.02-1.49 and 2.13-6.23 respectively; the selectivity coefficients of Co ion adsorption relative to Mg, K and Ca ions are 5.42-15.22, 1.02-2.36 and 1.06-32.68 respectively; the selectivity coefficients of Mn ion adsorption relative to Mg, K and Ca ions are 2.58-30.67, 1.05-2.93 and 1.15-13.66 respectively.

7. The P-type zeolite converted from mordenite according to claim 3, characterized in that: The adsorption capacities for Sr, Co and Mn ions in water are 76.71-150.86 mg / g, 38.65-113.26 mg / g and 42.57-120.69 mg / g, respectively.